مسح حقلي لمرض الذبول الفرتسليومي على أشجار الزيتون في محافظة اللاذقية (Latakia University Journal -Biological Sciences Series, 2017)
يعد مرض الذبول الفرتسليومي من أهم الأمراض التي تصيب الزيتون، وينتشر في معظم مناطق زراعته في العالم. يتسبب المرض عن الفطر Verticilliumdahliae, وهو من فطور التربة، واسع المجال العوائلي، ويشكل جسيمات حجرية تحتفظ بحيويته في التربة لفترة طويلة, ولا توجد طرائق ناجعة في مكافحتهحتى الآن.تم تنفيذ مسح حقلي لتحديد نسبة الإصابة وشدتها بهذا المرض على أشجار الزيتون في محافظة اللاذقية خلال عام 2015، شمل المسح جميع مناطق زراعة الزيتون في المحافظة. أظهرت النتائج أن أعلى نسبة إصابة وشدتها كانت على الصنف قيسي في منطقة القرداحة وبلغت( 10.68%، 4.05%) على التوالي، وأدناها على الصنف صفراوي في منطقة القرداحة (3.92% ,0.97%) على التوالي. Verticillium wilt is one of the most serious disease that affect olive trees, and it is spread all over the world where the olive trees grown. It is caused by the soil – borne fungiVerticilliumdahliaekleb. Whichhas a wide host range, and forms amicroseclerotia that survive for long time in the soil.and it is difficult to manage.In this studya survey was carried out in order to determine the incidence and severity of infection on olive trees in Lattakiaduring2015.The results showed that the highest percentage of infection and severity were on the Kaissicultivar in ALqurdaha (10.68% , 4.05%) respectively , and the lowest percentage of infection and severity were on the Safrawicultivar in ALqurdaha (3.92% , 0.97%) respectively.